1959
DOI: 10.1021/ac60154a029
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Petroleum Products in C12 to C20 Range. Application of FIA Separatory and Low Voltage Mass Spectrometric Techniques

Abstract: A procedure has been developed for determining the composition of petroleum products in the C12 to C20 range using FIA separations and standard and low voltage mass spectrometric techniques. The variation of low voltage sensitivities of aromatics with the number of substituents is used ro determine the average number of substitutions per benzene ring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

1961
1961
2000
2000

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 7 publications
(7 reference statements)
0
11
0
Order By: Relevance
“…The i described from Mass and NMR data. 6 From infrared to be the most probable positions of the substituent groups of assignment of positions is uncertain. These appear the main components.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The i described from Mass and NMR data. 6 From infrared to be the most probable positions of the substituent groups of assignment of positions is uncertain. These appear the main components.…”
Section: Resultsmentioning
confidence: 99%
“…The total concentration of each species, principally members of the CnH2n-6 and CnH2n_8 series, was computed from the principal parent ion only, that is the molecular ion containing the most abundant isotopes of carbon and hydrogen. Several investigators (3,6,7) have determined sensitivities of pure hydrocarbons of the series encountered in this investigation and have discussed the application of these sensitivity values to the analysis of petroleum fractions. Crable, Kearns, and Norris (3) have shown that the sensitivities of the alkylbenzenes depend markedly on the extent of substitution with the sensitivity increasing as the substitution in increased.…”
mentioning
confidence: 99%
“…In addition to saturated hydrocarbons, nonaromatic olefins, and oxygen-and nitrogen-containing "hetero" compounds, these cracked gas oils have been variously found to contain alkyl benzenes (4. 5,8,20), styrenes (9), naphthalenes (8-5, 8, 20), fluorenes (2) phenanthrenes (2-5, 7, 8), anthracenes (2, 4, 5, 7, 8), and pyrenes (3,4,7).…”
Section: Sample Monoaromaticsmentioning
confidence: 99%
“…The relative cross sections and mole sensitivities for LV/EI and FI of at least the lower molecular weight homologues in the -8 Z(H) through -22 Z(H) series have been correlated (14). Furthermore, the available data for LV/EI (15,16) and for FI (14) indicate that the relative mole sensitivities for compounds in a given hydrocarbon series become essentially independent of carbon number with the initial dependence on carbon number di- minishing as the number of condensed rings in the parent compound rises, i.e., as the specific Z(H) value becomes more negative. Since the ion intensity for compounds of a given carbon number in a specific -Z(H) series is proportional to the number of those species in the gaseous mixture, the close resemblance in the LV/EI and FI molecular-ion intensity distributions is expected.…”
mentioning
confidence: 98%
“…For aromatic compounds of interest in fossil-fuel mass spectrometry, fragment ions account for a considerably greater fraction of the cross sections for ionization by 70-eV electrons than for ionization by either ca. 10-eV electrons (15,16) or high-electric fields (14). Since the use of 70-eV rather than 10-eV electrons would increase the dynamic range of an analysis, especially as the resolution is increased, both the origin and generality of the phenomenon observed by comparing Figure 1 with Figures 2 and 3 deserve further investigation.…”
mentioning
confidence: 99%